Proposal Of Optimized Solutions For Joint Use And Hybridization Of Energy Storage Systems And Combined Cycles Or Renewable Energy Plants - Rodriguez-Arango, Rafael Olavarria (European Scientific Journal, ESJ, 2022)
This article describes an electrical energy storage system with a heat pump and steam accumulators or molten salt storage, and solutions are proposed for the hybridization of this storage system with power plants, mainly combined cycle and renewable, already existing or new construction. As a result of the development of these solutions, it is concluded that these hybridizations allow each one of the plants to operate with its nominal performance in peak hours and with a similar or higher performance in off-peak hours or periods of low prices, that is, , the electrical energy supplied to the network for each thermal or electrical kilowatt that feeds the plants is similar or higher when this electrical energy is previously stored. These high efficiencies after storage are achieved by combining heat pump performance (COP greater than 2) and Rankine cycle heat rate. In summary, it is possible to optimize the performance of the power plants during all hours of the day and optimize costs due to the joint use of equipment and systems. Highlights Hybridization combined cycles, renewables and electricity storage can become a useful tool.Hybridization can optimize the joint operation of the electrical system. Proposed hybridization achieves the same performances after storing the energy. Proposed hybridization allows sharing of equipment and systems.